A dynamic microporous magnet exhibiting room-temperature thermal hysteresis, variable magnetic ordering temperatures and highly selective adsorption for CO2. Issue 2 (22nd October 2018) - Liu, Zhong-Yi; Zhao, Hong; Song, Wei-Chao; Wang, Xiu-Guang; Liu, Zheng-Yu; Zhao, Xiao-Jun; Yang, En-Cui
Abstract : A dynamic microporous magnet exhibits a room-temperature hysteresis loop, variable magnetic ordering temperatures and high adsorption selectivity for CO2 over N2 . Abstract : A dynamic microporous magnet shows reversible temperature-tuned single-crystal-to-single-crystal transformations by stepwise losing of coordinated and lattice water molecules, exhibiting an unusually observed room-temperature hysteresis loop, variable magnetic ordering temperatures and high adsorption selectivity for CO2 over N2 .